HIBAH IN ESTATE PLANNING AND TAKAFUL - Nurul Natasha Daud; Hendon Redzuan; Rubayah Yakob (Journal of Islamic, Social, Economics and Development, 2017)
Islamic estate planning and managing risk is an important aspect that must be implemented by Muslims nowadays. While Muslims are encouraged to accumulate wealth, they must also know how to protect the property and also to distribute wealth. Therefore, Takaful comes as a measure to protect property and as risk management methods. On the other hand, hibah is defined as an instrument that can be applied to Islamic property planning. Therefore, hibah takaful is a concept where a person provides a takaful benefits to be given to the nominee when the required event of a disaster happens. The purpose of this study is to discuss how hibah can help a person to plan on their property especially during the occurrence of the required event of disaster. In addition, this study also explains the position of nominee hibah in takaful. The author uses qualitative methods of library reseach and field studies. From the results of this study, the author was in view that hibah can help people especially muslim in managing their property. This hibah takaful concept inteds to hep person especially muslims to provide Volume: 2 Issue: 5 [September, 2017] pp.30-39] Journal of Islamic, Social, Economics and Development eISSN: 0128-1755 Journal website: www.jised.com m 31 funds and protect their financial as well as a measure of misfortune wealth management planning